Production of shell tomato (Physalis ixocarpa Brot.) with vermicompost and chemical fertilization - Rivadeneyra-Manzanilla, José Eduardo; Palacios-Torres, Rogelio Enrique; Ramírez-Seañez, Ana Rosa; Hernández-Hernández, Hipólito; Amador-Mendoza, Adolfo (Ecosistemas y Recursos Agropecuarios, 2025)
The use of conventional fertilizers has been a viable production alternative for many years; however, it has caused serious damage to ecosystems. The objective of the present study was to evaluate the effect of chemical, organic and chemical-organic fertilization on morphology, fruit quality and yield of husk tomato under rainfed conditions. The experiment was carried out in completely randomized blocks with four treatments and three repetitions: T1 = 120N-80P-120K, T2 = 3.479 kg m2 of vermicompost, T3 = 120N-80P-120K + 3.479 kg m2 of vermicompost and T4 = witness. The results indicate that treatment 3 (chemical-organic) positively influenced the variables of morphology, yield and pH. The chemical-organic treatment obtained the best results for yield, while the content of total soluble solids did not present a significant difference between treatments. The use of chemical-organic fertilization is a production alternative that has a positive effect on the nutrition of shell tomato.